The effect of surface-modified silver nanoparticles on the inflammatory component of the intragingival peri-implant area - D. Ya. Maksymov; O. M. Mishchenko (Zaporožskij Medicinskij Žurnal)
Aim: to evaluate the intensity of the gingival inflammatory component in the peri-implant area by studying the mucous membrane bleeding in the implant area according to the papilla bleeding index (PBI), when using healing abutments with a surface modified with silver nanoparticles (AgNP).